Crack influence and fatigue life assessment in rail profiles: a numerical study - Urassa, Patrick; Habte, Haileleoul Sahle; Mohammedseid, Awel (Frontiers in Built Environment, 2023)
Rail transportation is a pivotal mode of land transport for its efficiency in transporting passengers and freight across short or long distances; hence, the reliability and safety of rail systems are of key importance. Rolling contact fatigue (RCF), characterized by the cyclic loading of wheel-rail contacts, presents a significant challenge in the rail industry. This study presents a comprehensive numerical investigation on the influence of different crack orientations on the contact stress of the rail profile and subsequently the fatigue life. Using finite element analysis (FEA) with Abaqus and FE-safe software, the study examined different crack orientations’ impact on stress distribution and fatigue life of rail profiles. Employing the extended finite element method (XFEM), this study modeled cracks in rail profiles with different orientations: parallel, perpendicular, and oblique to the rail axis. finite element analysis was used to obtain stress distribution results, highlighting the impact of crack presence, and orientation on maximum contact stresses. Subsequently, fatigue analysis was performed using FE-safe software, wherein the FEA results were imported to estimate fatigue life and damage evolution. The study revealed that the presence of a crack significantly influences contact stress, fatigue life, and damage accumulation. The results further demonstrated that crack orientation has an impact on the severity of those effects. Oblique cracks exhibited higher impact compared to lateral and longitudinal cracks. The study provides valuable insights into rolling contact fatigue-related failures, aiding in better understanding and mitigation of such issues, thereby contributing to improved rail maintenance practices and system safety.